2017
DOI: 10.1080/15627020.2017.1410074
|View full text |Cite
|
Sign up to set email alerts
|

Game fence presence and permeability influences the local movement and distribution of South African mammals

Abstract: Fences are utilized throughout the world to restrict the movements of wildlife, protecting them from threats and reducing human-wildlife conflict. In South Africa the number of privately-owned fenced game reserves has greatly increased in recent years, but little is known about how fencing affects the distribution and movements of target and non-target mammals. We surveyed 2m either side of the complete fence line of a recently established commercial game reserve in South Africa, identifying signs of animal pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 51 publications
2
14
0
Order By: Relevance
“…Of the 27 mammal species we recorded crossing the fence, carnivores and primates crossed most frequently, and crossing behaviors were strongly predicted by microhabitat at the crossing point, body size, and adjacency to the nearby Soysambu Conservancy. This result supports other studies that have shown primates and carnivores frequently move over, under, and through fence lines (Pirie et al, 2017). Most ungulates, on the other hand, faced difficulties crossing.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Of the 27 mammal species we recorded crossing the fence, carnivores and primates crossed most frequently, and crossing behaviors were strongly predicted by microhabitat at the crossing point, body size, and adjacency to the nearby Soysambu Conservancy. This result supports other studies that have shown primates and carnivores frequently move over, under, and through fence lines (Pirie et al, 2017). Most ungulates, on the other hand, faced difficulties crossing.…”
Section: Discussionsupporting
confidence: 90%
“…Our methods offer a novel approach for quantifying wildlife responses to fencing, and our findings are consistent with surveys and frequent observations that report wildlife regularly passing in and out of the park (Kassilly et al, 2008, but see also Elliot et al, 2020). Our findings also echo indirect assessments that have shown fences are permeable to many wildlife species elsewhere in Africa (e.g., Pirie et al, 2017).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In many parts of the world, wildlife is confined to fenced areas, and this is especially true in South Africa where it is a legal requirement to fence an area containing dangerous game species 8 , 12 . Although fences are often successful at confining cattle and large herbivores, fences are semi-permeable for many mammals including some large predators 13 15 . Holes under fences are created by erosion and by digging species 16 , and when a fence line is breached, species detect and exploit holes quickly 17 .…”
Section: Introductionmentioning
confidence: 99%
“…nature and the difficulty in quantifying their extent and impact. The level of maintenance or decay of a fence is essential to its effectiveness at its intended purpose and may drastically change its ecological effects (Pirie et al 2017). Keeping fences maintained has long been a central occupation of pastoralists, but now other fence builders have come to understand its importance.…”
Section: Figure 1 Fence or Not A Fence? Fences Require A Specific Anmentioning
confidence: 99%